Art Therapy Activities Using the Mood Journals to Enhance Emotional Awareness in Grade 3 Students at Prasartvidhyanonthaburi School - โตตาบ วรวิทย์; สุวรรณสัมฤทธิ์ ชลาภรณ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purpose of this study was to examine the emotional awareness ability of Grade 3 students after participating in art therapy activities using an emotion journal, and to investigate Grade 3 students’ satisfaction with the use of art therapy activities through an emotion journal. This research adopted a quasi-experimental design, specifically a one-group pretest–posttest design. The sample group consisted of 49 Grade 3 students in the 2025 academic year from Prasartvidhyanonthaburi School, Nonthaburi Province, selected through Simple Random Sampling) sampling. The experiment consisted of 8 sessions conducted over four weeks period. The research instruments included art therapy activities using an emotion journal, an emotional awareness ability assessment for Grade 3 students, and a satisfaction questionnaire regarding Grade 3 students’ use of art therapy activities through an emotion journal. Three experts were invited to review and consider the content validity, language accuracy, and appropriateness of the questions. The Index of Item–Objective Congruence (IOC) was used to determine the consistency of each item with the research objectives. The acceptable criterion for the IOC value for each item was at 0.67. Statistical data analysis was conducted using basic statistics, including the mean and standard deviation. The research findings revealed that Grade 3 students of Prasartvidhyanonthaburi School have emotional awareness ability after participating in art therapy activities using an emotion journal (M = 62.35) was higher than before the intervention (M = 55.65). Additionally, the overall satisfaction of Grade 3 students toward the use of art therapy activities through an emotion journal was at a high level.